2021
DOI: 10.1097/aog.0000000000004592
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Vaginal Panel Assay Compared With the Clinical Diagnosis of Vaginitis

Abstract: OBJECTIVE: To compare the performance of vaginitis diagnosis based on clinical assessment to molecular detection of organisms associated with bacterial vaginosis, vulvovaginal candidiasis, and Trichomonas vaginalis using a vaginal panel assay. METHODS: This cross-sectional diagnostic accuracy study included 489 enrolled participants from five collection sites where those with vaginitis symptoms had a vaginal assay swab collected during their visit and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…6 In our analysis, 50% of the women represented in this database did not receive any laboratory-based testing but instead received a vaginitis diagnosis based on clinical presentation without documentation of the use of microscopy, which decreases sensitivity and specificity of diagnosis. A recent study demonstrated that, compared with NAAT-based detection, clinician-based diagnosis of vaginitis with microscopy misses ~42% to 72% of vaginitis cases, depending on the cause, 20 which would place the chance of accurate diagnosis within our cohort even lower. Implementation of laboratory-based testing improves sensitivity for detection of vaginitis, with little to no decrease in specificity.…”
Section: Discussionmentioning
confidence: 79%
“…6 In our analysis, 50% of the women represented in this database did not receive any laboratory-based testing but instead received a vaginitis diagnosis based on clinical presentation without documentation of the use of microscopy, which decreases sensitivity and specificity of diagnosis. A recent study demonstrated that, compared with NAAT-based detection, clinician-based diagnosis of vaginitis with microscopy misses ~42% to 72% of vaginitis cases, depending on the cause, 20 which would place the chance of accurate diagnosis within our cohort even lower. Implementation of laboratory-based testing improves sensitivity for detection of vaginitis, with little to no decrease in specificity.…”
Section: Discussionmentioning
confidence: 79%
“…Diagnostic accuracy can be improved using one of the new vaginal panel assays such as BD MAX Vaginal Panel (Becton, Dickinson and Company). 3…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…As noted above for BV, the vaginal panel assay improves the accuracy of clinical diagnosis. 3 Culture usually is indicated only in patients with infections that are refractory to therapy.…”
Section: Candidiasismentioning
confidence: 99%